Spectrophotometric Analysis of Amoxycillin in Tablets Using Hydrotropic Solubilization Technique - Maheshwari, R.K. (Asian Journal of Chemistry, 2010)
In the present investigation, hydrotropic solution of urea (10.0 M) was employed to solubilize amoxycillin trihydrate (a poorly water-soluble drug), from fine powder of its tablets, to carry out spectrophotometric analysis. Beer's law was obeyed in the concentration range of 50-350 μg/mL at 274 nm. Recovery studies and statistical data proved the accuracy, reproducibility and the precision of the proposed method. Presence of urea and commonly used tablet excipients did not interfere in the spectrophotometric estimation.